Determinants of Energy Consumption in Egypt “New Approach” - Abdallah Mostafa, Mohammed Galal; Selmey, Mousa Gowfal Selmey Gowfal (International Journal of Energy Economics and Policy, 2022)
In Egypt, policymakers are particularly concerned about energy consumption. So, The goal of this study is to look into the factors that influence Egyptian energy consumption. The study applied a new approach known as artificial neural network (ANN) from 2000 to 2020 to achieve this goal. according to the results of this study, global energy prices are the most important determinants of Egyptian energy consumption, followed by economic growth and trade openness. Other factors such as population growth, inflation, urbanization, and industrialization, which have been highlighted in other papers, are not determinants of Egyptian energy consumption. this research recommends that need to follow policies that rationalize energy consumption and improve the efficiency of its use